2013
DOI: 10.1007/s11606-013-2534-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of an Intimate Partner Violence Screening Tool for Female VHA Patients

Abstract: OBJECTIVES: Female Veterans are at high risk for physical, sexual, and psychological forms of intimate partner violence (IPV) victimization. This study evaluated the accuracy of a brief IPV victimization screening tool for use with female Veterans Health Administration (VHA) patients. DESIGN: Participants completed a paper-and-pencil mail survey that included the four-item Hurt/Insult/ Threaten/Scream (HITS) and the 39-item Revised Conflict Tactics Scales (CTS-2). Operating characteristics, including sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 30 publications
4
54
0
1
Order By: Relevance
“…Responses are scored on a 5-point scale from 1 ("never") to 5 ("frequently") and summed for a total score. Consistent with prior work demonstrating that a cutoff score of 6 optimizes the sensitivity and specificity of the HITS in detecting IPV among female VHA patients, 10,13 women who scored Ն6 screened positive for past-year IPV.…”
Section: Ipv Screensupporting
confidence: 80%
See 2 more Smart Citations
“…Responses are scored on a 5-point scale from 1 ("never") to 5 ("frequently") and summed for a total score. Consistent with prior work demonstrating that a cutoff score of 6 optimizes the sensitivity and specificity of the HITS in detecting IPV among female VHA patients, 10,13 women who scored Ն6 screened positive for past-year IPV.…”
Section: Ipv Screensupporting
confidence: 80%
“…As described elsewhere, 10 surveys were mailed to potential participants using a modified multiple mailing strategy 11 : (1) informed consent fact sheet, survey packet, and $10 incentive; (2) 2 weeks later a thank you/reminder postcard; and (3) 4 weeks later an additional survey packet and $10 incentive to nonresponders. The local institutional review board approved all procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Regional studies examining VHA users found even higher rates of IPV, with up to 28.8% of partnered women reporting past-year IPV in mail survey studies. 15,16 Understanding patient-level factors that are associated with past-year IPV may help tailor programs to patients most at risk. The USPTF cites IPV risk factors such as younger age, substance abuse, and economic hardship.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of JGIM, Iverson et al 1 report on the accuracy of a brief IPV screening tool in a population of female Veterans Health Administration (VHA) patients. Participants completed a mailed survey consisting of the IPV reference "gold" standard [the 39-item Revised Conflict Tactics Scale (CTS-2)] compared with HITS, a brief screening tool consisting of four items that asks about physical hurts, insults, threats or screams over the prior 12 months.…”
mentioning
confidence: 99%